2017
DOI: 10.1002/jtr.2148
|View full text |Cite
|
Sign up to set email alerts
|

A study on country images, destination beliefs, and travel intentions: A structural equation model approach

Abstract: This study explores how individuals' cognitive and affective country images influence destination beliefs, and how these beliefs are associated with individuals' travel intentions. With the product country image and tourism destination image literature, we develop four hypotheses that are tested using structural equation modeling. We use a sample of 605 Japanese respondents. Our results indicate that the cognitive country image is positively associated with the affective country image. The findings suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
1
25
1
2
Order By: Relevance
“…Information given by tourists about the destination image was significant because potential travelers mostly relied on the opinions and advice provided by those users who have experienced the same services [56], and therefore a perceived image of a target location positively and significantly influenced the tourists' attitudes [112]. In contrast, our findings were not in line with previous studies [113][114][115]. Artuger and Cetinsoz [114] examined the impact of destination image (cognitive image and affective image) on revisiting intention and concluded that affective image positively, but insignificantly, influenced travel intention.…”
Section: Discussioncontrasting
confidence: 86%
“…Information given by tourists about the destination image was significant because potential travelers mostly relied on the opinions and advice provided by those users who have experienced the same services [56], and therefore a perceived image of a target location positively and significantly influenced the tourists' attitudes [112]. In contrast, our findings were not in line with previous studies [113][114][115]. Artuger and Cetinsoz [114] examined the impact of destination image (cognitive image and affective image) on revisiting intention and concluded that affective image positively, but insignificantly, influenced travel intention.…”
Section: Discussioncontrasting
confidence: 86%
“…In addition, some studies have employed frameworks that measured the two dimensions of destination image individually [51]. As a result, there have been partly mixed results when researchers have tried to delineate the cognitive country image/affective country image relationship [52]. However, in line with recent studies' prior conclusions, this study confirms the positive effect of cognitive image on affective image.…”
Section: Discussionsupporting
confidence: 76%
“…Cluster analysis is also unable to determine to what extent a certain characteristic has an influence on the probabilities of visiting a place. Other studies, such as the one carried out by Lindblom, Lindblom, Lehtonen, and Wechtler (), have used data processed by structural equations modeling to establish the travel intentions of tourists within destinations. Although this technique can identify the variables that explain a certain event, it presents some limitations.…”
Section: Literature Reviewmentioning
confidence: 99%